A review of varicocele treatment and fertility outcomes. (15th March 2022) - Maheshwari, Abha; Muneer, Asif; Lucky, Marc; Mathur, Raj; McEleny, Kevin; ,
Abstract: Varicoceles are reported to be present in a significant proportion of men presenting with subfertility and are more common amongst this group than in the general population. Opinion still remains divided amongst clinicians managing male factor infertility as to whether varicoceles alter the probability of spontaneous conception and/or pregnancy and live birth rates after fertility treatment. The debate as to whether varicoceles should be treated or not has intensified in recent years. This is due to the concerns regarding the impact of varicoceles on not only conventional semen parameters, but also the potential effects that they may have at the cellular level (an increase in circulating reactive oxygen species (ROS) resulting in sperm DNA fragmentation, even when conventional semen parameters are within the normal reference ranges). It has been suggested that treating the varicocele may result in improvements in the semen parameters, the fertilization and pregnancy rates for both spontaneous pregnancy as well as following in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) treatment. ICSI can still be used for Assisted Reproduction Treatment (ART) in the presence of suboptimal semen parameters. However, it is an invasive and expensive technique with potential adverse effects on the offspring. As far as we are aware, there are no randomized controlled trials comparing the clinical/cost effectiveness of varicocele treatment versus the immediate use of ICSI on pregnancy rates. Previous modelling exercises are old and do not take into consideration current practices and trends such as rising female age and time to pregnancy. The conflicting advice that patients sometimes receive, challenges our commitment to evidence-based practice. The only way to resolve the controversy is to undertake an appropriately powered randomized trial, assessing clinical- and cost-effectiveness and the time to pregnancy following varicocele treatment and comparing this to a no treatment group.